The epidemiology of physical disability among elderly in Kota Bharu, Kelantan - Dahalan, Latifah; Ismail, Ab. Aziz Al-Safi; Ag. Mat, Hamzah (Pusat Pengajian Sains Perubatan, Universiti Sains Malaysia, 2004)
Globally, the decline in fertility and mortality as well as improvement in life expectancy ·were said to be responsible for the aging population by the year 2020. In Malaysia, the elderly population was 1.2 million or 5. 9% of the 20 million total population in the country in 1995. This number was projected to increase to 11.3% by the year 2020. Elderly population are prone to get physical disability as well as chronic medical illnesses. This is a cross-sectional study to determine the prevalence of physical disability and its associated risk factors among elderly, aged 60 years and above. A total of 270 participants were taken randomly under 3 health clinics under Kota Bharu oper~tional !areas by using multistage sampling. Guided- questionnaire were administered and the subjects were asked to go to clinics or community centre on the appointed date for physical e~amination and blood taking for fasting blood sugar and total cholesterol. Physical disability was measured by activities of daily,living ( ADLs) and instrumental's activities of ~aily living ( IADLs). ADLs is comprise of bathing, dressing, going to toilet, transferring from bed or chair, continence, and feeding. Whereas IADLs encotnpass the following domestic function : using the telephone, using transportation, shopping, cooking, house-keeping, taking medication and budgeting. The IADLs methods offer indicators of" applied " problem that extend the disability theme of ADLs scales to include some elements of handicap concept.Physical disability was defined as the inability to accomplish one or more ADLs or IADLs.Separate multiple logistic regression was used to determine the risk factors for both physical disabilities. The prevalence of physical disabilities in ADLs and IADLs were 10.7% ( 95% CI: 7, 14) and 34.8% ( 95% CI: 29, 41) respectively. Significant risk factors of ADLs were age (OR=2.669, 95%CI: 1.1 07, 6.643), hearing impairment (OR= . 2.539, 95%CI: 1.034,6.233), diastolic blood pressure (OR= 3.803, 95%CI:1.249, 11.578), and total cholesterol (OR= 1.535, 95%CI: 1.071, 2.200).Wherea~ for IADL were age (OR=2.391, 95%CI: 1.185,4.827), income (OR= 0.219, 95%CI:0.078, 0.615),diastolic blood pressure (OR=2.023, 95°/oCI: 1.038,3.941 ), marital status (OR=2.378, 95%CI:1.227,4.609 ) and obesity (OR=4.679,95%CI:l.544, 14.182). There was a strong significant association between ADLs and IADLs (OR=9.012, 95%CI:3.400, 23.887). The prevalence of physical disability for ADLs and IADLs were 10.7% and 34.8% respectively and it was similar with others studies. These findings also suggested that certain sociodemographic characteristics ( i.e age, income & marital status ), life-style behavior ( obesity) and medical illnesses (hearing impainnent, total blood cholesterol and high diastolic blood pressure) were significant risk factors of physical' disability in elderly. Physical disability in ADLs was a strong predictor for physical disability· in IADL. The majority of predictors of physical disability that were identified by this study are potentially subject to modification either by treatment, life-style change or special device. Public health efforts to reduce prevalence of all these factors in both sexes should continue.